Partially four-vessel umbilical cord: about a diagnosed case at Panzi hospital - D., Boengandi Walala; O., Nyakio Ngeleza; B., Mukanire Ntakwinja; G., Katenga Bosunga; D., Mukwege Mukengere (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Umbilical cord malformations are described in the literature; and it's about the umbilical artery and the umbilical vein. There are sometimes cases of a single umbilical artery. In contrast, the number of vessels in the umbilical cord can increase by three to four. A supernumerary umbilical vein is particularly rare and is usually found in association with congenital anomalies; sometimes the supernumerary umbilical vein is associated with no malformation. We report a case of umbilical cord having a four-vessel part diagnosed at the maternity ward of Panzi Hospital, in the town of Bukavu, South Kivu, DR Congo.